Protocol for optical detection of iodide ions in aqueous environments using a zirconium(IV)-enhanced strategy - Tiantian Feng; Xuran Chen; Shilei Zhao; Meng Cao; Lijuan Feng; Se Shi; Hui Wang; Tao Liu; Yihui Yuan; Ning Wang (STAR Protocols, 2023)
Summary: Detection of radioactive iodide ions (I–) is important for protecting human beings from the hazards of radioactive pollution. Herein, we present a protocol for detecting I– using a zirconium(IV)-enhanced strategy. We describe steps for optimizing the I– detection approach, establishing standard curves, and finally applying the approach. The use of zirconium(IV) greatly improves the detection performance and endows this approach with an ultralow detection limit of 0.176 nM together with wide applicability in various aqueous environments.For complete details on the use and execution of this protocol, please refer to Feng et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.